Analisis Pemahaman Konsep Mahasiswa pada Pembelajaran Volume Benda Putar Berbasis Maple - Dison Linome; Yusak Imanuel Bien; Urni Babys (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
Concept understanding is recognizing all  of the materials, which the students not only know and understand but able to show the concept in from that easy to understand and also able to aplicated. The aim of this study is to analysis the concept understanding for the student in learning volume of revolution based on maple. This research method is descriptive qualitative. The participants of this study are the student of the mathematics education study program STKIP Soe who took integral calculus courses totaling 14 students. Research data were collected through observation, tests and interviews. The data analysis technique used is qualitative data analysis following the Miles and Huberman model. Test the validity of the data used is the extension of observations, triangulation techniques and negative case analysis. The results showed that learning the volume of a maple-based rotary object can help students understand the concept. Students in solving rotary object volume questions manually or the maple method show that most students have been able to achieve indicators of understanding mathematical concepts. Based on the results of this study, it is also known that there are still students who have not reached the indicator of concept understanding due to miscalculations and using the wrong concept in solving test questions on the material of rotating object volume due to the absence of students during the lecture process